Design Of A Clean Water Distribution Pipe System For Ngenep Village Based On Projected Water Needs For The Next Ten Years - Andi Nur Rasyidi; Dimas Syafriel Naufal Alif; Sari Nefiyanti Zulkarnain (CV. AFDIFAL MAJU BERKAH, 2026)
Ngenep Village, Karangploso District, Malang Regency, is experiencing a clean water crisis due to population growth of 13,124 people (2024) and residential urbanization without integrated distribution from the Umbulan (93 l/s) and Nyolo (34 l/s) sources. This study aims to design a distribution pipe system, reservoir, and pump based on a 10-year water demand projection (SNI 7509:2011). Using mixed methods, dominant quantitative, the population of 13,124 people of Ngenep Village was sampled in total for the Umbulan-Nyolo zone. Instruments include WaterCAD (Hazen-Williams), ETABS, current meters, with arithmetic projection analysis (deviation test σ=1.36; R²=1.00), hydrogeology, and hydraulic simulation. The results show a population projection of 19,005 people (2034), HDPE PE100 SDR17 network (Ø2